2015
DOI: 10.1007/s00405-015-3775-6
|View full text |Cite
|
Sign up to set email alerts
|

Lateral semicircular canal fistula in cholesteatoma: diagnosis and management

Abstract: The objective of this retrospective study was to present the authors' experience on the management of labyrinthine fistula secondary to cholesteatoma. 695 patients, who underwent tympanoplasty for cholesteatoma, in a University Hospital between 1993 and 2013 were reviewed, to select only those with labyrinthine fistulas. 42 patients (6%) had cholesteatoma complicated by fistula of the lateral semicircular canal (LSCC). The following data points were collected: symptoms, pre- and postoperative clinical signs, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
47
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 34 publications
7
47
1
2
Order By: Relevance
“…In our study, these rates were 7 and 7%, respectively. Like Jang et al [ 10 ], Meyer et al [ 18 ] and Sone et al [ 19 ], we found no correlation between fistula size and postoperative BCT. Ikeda et al [ 20 ] did find a correlation between fistula size and poorer postoperative BCT.…”
Section: Discussionsupporting
confidence: 70%
“…In our study, these rates were 7 and 7%, respectively. Like Jang et al [ 10 ], Meyer et al [ 18 ] and Sone et al [ 19 ], we found no correlation between fistula size and postoperative BCT. Ikeda et al [ 20 ] did find a correlation between fistula size and poorer postoperative BCT.…”
Section: Discussionsupporting
confidence: 70%
“…Another complication related to cholesteatomas is the erosion of the semicircular canals, mostly the lateral canal, as it is placed nearer to the antroattical region where most cholesteatomas arise. CT-scans are able to predict these labyrinthine fistulas with a sensitivity of > 80% [5]. Several inner ear malformations, such as Michel's aplasia, common cavity deformity, cochlear aplasia or hypoplasia, semicircular canal aplasia or dysplasia, enlarged vestibular aqueduct, and Mondini dyplasia have been described.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with chronic suppurative otitis media with cholesteatoma a labyrinthine fistula has been confirmed in 3–13% of patients that underwent a surgical procedure [3]. …”
Section: Introductionmentioning
confidence: 99%